Development of Kampong Kopi Camp as an Eco-Tourism Destination Based on Circular Economy - Martiningsih, Ni Gst Ag. Gde Eka; Suryana, I Made; Swaputra, Ida Bagus Made (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This study aims to analyze internal and external factors in the development of Kampung Kopi Camp and analyze strategies in the development of Kampung Kopi Camp in Batungasel Village, Pupuan Subdistrict, Tabanan Regency, the withdrawal of samples from the population was carried out deliberately (purposive sampling). The method used in this study is to use the SWOT analysis method and the results showed that the internal factors of tourism development strategies in Kampung Kopi Camp in Batungasel Village, Pupuan District, Tabanan Regency, from the main strength factors, namely strategic location and place and the main weakness in tourism development strategies in Kampung Kopi Camp, namely less than optimal promotion. While the external factors of tourism development strategies in Kampung Kopi Camp in Batungasel Village, Pupuan District, Tabanan Regency from the opportunity factor, namely government policies to support tourism development and threat factors in Kampung Kopi Camp tourism, namely quite a lot of competitor factors. The main strategy in developing tourism in Kampung Kopi Camp in Batungasel Village, Pupuan District, Tabanan Regency is to cooperate with the tourism office to develop tourism in the future.